PERWUJUDAN PANCA TUGAS GEREJA DALAM KEHIDUPAN SEHARI-HARI KELUARGA KRISTIANI DI STASI HATI KUDUS YESUS BULAK SUMBERSARI - Yohanes Eko Priyanto; Cornelius Triwidya Tjahja Utama (Lembaga Penelitian STKIP Widya Yuwana, 2017)
The life of the Church as the people of God is obvious in the involvement of members of the Church who implement the five tasks of the Church such as evangelization (kerygma), communion (koinonia), liturgy (liturgia), service (diakonia), and testimony (martyria). The members of Church appear to be real inlife of the christian family. Christian family is a Small Church or Church of Household (Ecclesia Domestica) which consists of parents and children who have beenbaptized. Therefore, christian family have an important mission to develop and support the Church by implementing five tasks of the Church in daily life. Inreality, there are christian families who do not understand about five tasks of the Church. The are christian families are less concerned with his family life. There are christian families are less active in the Church dan society. From the above issues, formulated of research problems: what is the mean of five tasks of the Church? What is the mean of christian family? What extent christian family implement the five tasks of the Church in daily life? Therefore, this scientific paper was written in order to steeped of five tasks of the Church, steeped of christian family, and to know extent christian family implement the five tasks of the Church in daily life. This research use qualitative method. The respondents are christian family in Stasi Hati Kudus Yesus, Bulak Sumbersari. Generally, this research showsthat any christian families have not understood about five tasks of the Church. Nevertheless, christian families have implemented the five tasks of the Church in daily life such as family, Church and society.